Gender and cultural aspects of brucellosis transmission and management in Nakasongola cattle corridor in Uganda - Christine Tricia Kulabako; Stella Neema; Lesley Rose Ninsiima; Jörn Klein; Lydia Namakula Nabawanuka; James Muleme; Javier Sánchez Romano; Peter Atekyereza (PLoS ONE, 2025)
Background Brucellosis is a zoonotic disease with significant public health and economic effects on societies. In Uganda, brucellosis is endemic and a primary contributor in livestock productivity losses. This is more worrisome for populations in the cattle corridor with high reliance on cattle and milk for nutritional value and symbol in social relations and identity. The community’s social construction may affect comprehension of brucellosis hence leading to exposure and increased vulnerability to transmission. Despite brucellosis’ high prevalence in the cattle corridor, little attention has been paid to its social construction. Hence, this study explored the interplay between gender dynamics, vulnerability and social construction of brucellosis transmission, in consideration of the unique socio-cultural context that characterizes cattle corridor populations. Methods Using an exploratory qualitative approach, the study was conducted in Nakasongola cattle corridor within three sub counties; Nabiswera, Nakitoma and Wabinyonyi using key informant interviews (KIIs) and focus group discussions (FGDs). Purposive sampling was used to identify participants for the four FGD [8–12] each from a subcounty though one was combined and 15 KIIs. Data were collected using face -to -face interviews with an interview guide that was structured using the Socio Ecological Model of Human Behaviour framework (SEMHB) constructs. Thematic analysis was conducted in NVivo 12 Pro incorporating both deductive (guided by the SEMHB) and inductive approaches (guided by the data). Findings The study identified important themes under each SEMHB influence level (Individual, Interpersonal, Community and Societal level). The study indicates that social composition and role distribution are driven by social and cultural expectations and significantly contribute to exposure and vulnerability to infection in the cattle corridor. For instance, it is paramount that women undergoing marriage preparations to be fed on raw milk for a certain period prior to their ceremony to enhance beauty. Also, important to note that use of personal protection to assist births is viewed by the community as opposing cultural norms, creating a perception of detachment from the highly valued cattle. Another noteworthy finding is the level of knowledge on brucellosis in terms of symptoms, transmission route, prevention and treatment at the interpersonal level. Furthermore, findings show practices such as the consumption of raw milk and assisted births, as being rooted in the social cultural norms, hence critical for transmission of brucellosis. At the community and organizational levels, the findings indicate an inadequate level of knowledge sharing and reluctance towards preventive measures as structural factors for the transmission of brucellosis and are ingrained in family and power relations. Conclusion The findings highlight that the social construction of brucellosis transmission is rooted in gender roles, social- cultural and power structures highlighting the influence of living process and spaces, at the different societal levels. Such complex dynamics play a critical role in determining individuals’ susceptibility to infection as well as transmission potential of the disease-causing agent in cattle keeping communities. The gendered induced vulnerabilities related to the socio-cultural norms and familial roles, also play an important role in the exposure and spill over at the individual, interpersonal and community levels. The insufficient knowledge-sharing and reluctance to adopt preventive measures emerge as structural contributors to the persistence of brucellosis and other emerging zoonoses. These factors, intertwined with family dynamics and power relations, call for targeted interventions that address both individual behaviors and broader socio-cultural and institutional barriers to effective disease management and prevention. Conversely, policies that align with the community’s social construction, gender and context are more likely to be feasible, adopted and sustained by the affected population.